2018
DOI: 10.1103/physrevd.98.024040
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational waves from asymmetric oscillon dynamics?

Abstract: It has been recently suggested that oscillons produced in the early universe from certain asymmetric potentials continue to emit gravitational waves for a number of e-folds of expansion after their formation, leading to potentially detectable gravitational wave signals. We revisit this claim by conducting a convergence study using graphics processing unit (GPU)-accelerated lattice simulations and show that numerical errors accumulated with time are significant in low-resolution scenarios, or in scenarios where… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 37 publications
1
70
0
Order By: Relevance
“…with 128 3 lattice points and throughout the time period considered in this Letter. We have noted the failure of a convergence test in our paper [1], and also a recent paper [2] has made this observation.…”
supporting
confidence: 63%
“…with 128 3 lattice points and throughout the time period considered in this Letter. We have noted the failure of a convergence test in our paper [1], and also a recent paper [2] has made this observation.…”
supporting
confidence: 63%
“…In the KKLT case the star mass is M P |W 0 | −1 V. We determined the field profile and the mass-radius behaviour for each case in the dilute regime. 36 A summary of the configurations obtained in this article can be seen in table 2 and a summary of expected mass ranges and radii for typically considered values of the overall volume and flux parameter are shown in figure 9. Similarly studying the formation of these objects we pointed out that the first condition listed at the beginning of section 4 (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…the existence of a localized overdensity) is always satisfied independently of the initial conditions and of the details of the model. The enhancement of the density perturbations takes place if there 36 The relation of the mass of the object with the inverse mass of the corresponding particle is reminiscent of the fact that in gauge theories elementary particles have masses proportional to couplings and that of the solitonic objects to powers of the inverse couplings. This played a role in uncovering strong-weak dualities in field and string theories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of studies on gravitational waves emitted during the formation of oscillons can be found in the recent literature [29][30][31][32][33][34][35][36][37][38]. In this paper, we try to address the following question: How much do the properties of gravitational waves emitted from the formation of oscillons, such as the shape and the amplitude of the power spectrum, depend on the potential of a source scalar field.…”
Section: Jhep03(2021)021mentioning
confidence: 99%